High Efficiency Single Phase Inverter Design - Didi Istardi; Basyir Halim; Arif Juwito Febriansyah (IAES Indonesia Section, 2017)
The solar power plant is one of the renewable energy that already was implemented in around the world. The important component in the renewable power plant is inverter device that convert the direct current to alternating current. The problem in the inverter are power quality, harmonics, and grid system. This paper introduced design inverter single phase with totem pole circuit. The circuit reduces losses in inverter. Besides that, DC link in PCB, component placement configuration, and adding filter in the output of inverter was implemented in the design. The result shown that the inverter have optimum efficiency at 98.67% and have a small total harmonics distortion with LC load.